Optimalisasi Perlindungan Merek Dagang bagi UMKM pada Era Kecerdasan Buatan di Wilayah Banyumas - Maya Ruhtiani; Pentadi Teguh Setiyanta; Monica Puspa Dewi (LPPM Universitas Harapan Bangsa Purwokerto, 2026)
Trademark protection plays a crucial role in supporting the sustainability and competitiveness of Micro, Small, and Medium Enterprises (MSMEs), particularly in responding to developments in digital technology and artificial intelligence. This community service program was conducted to enhance the legal awareness and technical skills of MSMEs in Banyumas in the process of trademark registration and digital monitoring. The implementation methods included preliminary observation, problem identification, legal counseling, technical training on electronic registration through the Directorate General of Intellectual Property, and the introduction of digital-based trademark monitoring tools. The results indicate an increase in participants' understanding of the importance of trademark protection, their ability to prepare administrative documents, and their capacity to utilize technology for independent monitoring. The discussion demonstrates that an experience-based educational approach combined with structured mentoring effectively promotes MSME engagement in legal processes. This program contributes to strengthening the legal and digital capacity of MSMEs in addressing legal challenges within the context of digital transformation.